Jual Beli Dua Harga dalam Satu Transaksi Jual Beli (Studi Komparatif Antara Mazhab Maliki dan Mazhab Syafi’i) - Ronny Mahmuddin; Zulfiah Sam; Akhmad Hanafi Dain Yunta; Mariyani Syam (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to find out and understand how to buy and sell two prices in one sale and purchase transaction (Bai'atani fi bai'ah) according to the perspective of the Maliki Sect and the Shafi'i Sect. The study was a qualitative descriptive research (non-statistical), which focuses on the study of manuscripts and texts, using a normative and philosophical approach. The results of the study found several things. First, according to the Maliki Sect, buying and selling two prices in one trade transaction (Bai'atani fi bai'ah) is permissible provided that there is certainty of an agreement to be used to pay before parting. While the Shafi'i sect considers that buying and selling is absolutely haram, this is due to the vagueness of the contract chosen by both parties. Second, the view of the Maliki Sect is skewed stronger than the view of the Shafi'i Sect, because Imam Malik considers this trade should not be unless there is clarity of agreement agreed before separation. The determination between the two agreements makes this trade permissible according to Imam Malik. As for the opinion of Imam Shafi'i is more careful, because such a trade is very vulnerable to injustice, usury practice and other damage, so at one time this opinion can also be used.